Minimally invasive function-preserving surgery based on sentinel node concept in early gastric cancer - Takeuchi, Hiroya; Kitagawa, Yuko (Translational Gastroenterology and Hepatology; Vol 1 (March 2016): Translational Gastroenterology and Hepatology, 2016)
Recent meta-analyses and a prospective multicenter trial of sentinel node (SN) mapping for early gastric cancer have shown acceptable SN detection rates and accuracy of determination of lymph node status. A dual-tracer method that employs radioactive colloids and blue dyes is currently considered the most reliable method for the stable detection of SNs in patients with early gastric cancer. However the new technologies such as indocyanine green (ICG) infrared or fluorescence imaging may revolutionize the SN mapping procedures in gastric cancer. For early stage gastric cancer, the establishment of individualized, minimally invasive treatments based on SN concept can retain the patients’ quality of life (QOL). The combination of non-exposed endoscopic wall-inversion surgery (NEWS) with SN biopsy is expected to become a promising, ideal minimally invasive, function-preserving surgery to cure cases of cN0 early gastric cancer.